2016
DOI: 10.11138/ccmbm/2016.13.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Densitometric evaluation of bone-prosthetic counterface in hip and knee arthroplasty with modern implants

Abstract: SummaryIntroduction. Recent acquisitions of the complex mechanisms of osseointegration between implants and host bone have gained attention, accordingly to the methods of evaluation of these interactions. DEXA analysis is considered an useful tool to assess such phenomena, in order to analyse in a quantitative manner the local metabolic activity of the bone, and to evaluate over the time the integration between host bone and prosthetic components. The purpose of the present study is to report about a prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Therefore, the integration of the implant prosthesis and the host bone on the interface and the promotion of host bone regeneration have become a momentous indicator for evaluating prostheses performance. The nature of the interaction between the joint prosthesis and host bone interface is actually the process of bone formation and resorption ( Lepri et al, 2016 ). Bone mesenchymal stem cells (BMSCs) play an important role in bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the integration of the implant prosthesis and the host bone on the interface and the promotion of host bone regeneration have become a momentous indicator for evaluating prostheses performance. The nature of the interaction between the joint prosthesis and host bone interface is actually the process of bone formation and resorption ( Lepri et al, 2016 ). Bone mesenchymal stem cells (BMSCs) play an important role in bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…The dual-energy X-ray absorption assay (DEXA) is a well-established method for monitoring patients after THA 11 . DEXA can detect small changes in BMD around a stem 12,13 , therefore, it is considered as the most reliable method of assessing periprosthetic bone stress shielding and proximal femur remodeling after THA 14 .In recent years, various types of cementless short stems have been introduced; however, little is known about bone remodeling and periprosthetic BMD associated with them. Several studies have reported that cementless short stems might reduce periprosthetic bone loss in the proximal femur compared with that associated with traditional THA 15,16 .…”
mentioning
confidence: 99%
“…The dual-energy X-ray absorption assay (DEXA) is a well-established method for monitoring patients after THA 11 . DEXA can detect small changes in BMD around a stem 12,13 , therefore, it is considered as the most reliable method of assessing periprosthetic bone stress shielding and proximal femur remodeling after THA 14 .…”
mentioning
confidence: 99%
“…The average age was 62.0 ± 7.4 years (range, 47 to 77 years) in the RM group and 61.6 ± 6.9 years (range, 47 to 75 years) in the IT group (p = 0.532). Dual xray absorptiometry (DXA) is a well-validated procedure for measuring BMD with the total hip implant in situ [14][15][16][17][18] . We used the QDR 4500 Elite device (Hologic) for our measurements.…”
mentioning
confidence: 99%